Marvel-verse. Thor. - Langridge, Roger (Marvel Worldwide, Inc, 2021)
Compilation of comics in Marvel's Thor series which chronicles Thor's banishment to Earth by his father Odin, where he meets scientist Jane Foster, takes on various villains, and is pitted against his jealous trickster brother Loki.